The impact of good corporate governance implementation and fundamental factors on company’s market performance (a study of listed companies in indonesia stock exchange in 2010-2013) - Dwijayanti, Mita; Soekarno, Subiakto (The Indonesian Journal of Business Administration, 2016)
Abstract -  GCG implementation was believed will help companies and countries which were in a cricis condition rising towards to a better conditions, competitive and restore the investor confidences. Therefore, the improvement of GCG implementation in Indonesia, especially for Publicly Listed Companies became main priority because it was one of the companies’ key to successful growth as well as giving long term benefits for the companies to win the bussiness competition. Many efforts were made to improve awareness of all parties about the importance of GCG implementation in Indonesia, as well as IDX which always try to improve GCG implementation of Listed Companies.This research was done to find out the impact of GCG implementation to the market performance of the companies which listed in IDX. GCG implementation will be proxied by the value of Corporate Governance Perception Index (CGPI). While company’s market performance will be proxied by PBV ratio. Besides, this research also try to find out the impact of fundamental factors, such as ROE, ROA, DER, growth and firm size to PBV. It was done to know what should be done by IDX to improve GCG implementation of the Listed Companies. This research uses multiple regression model in SPSS to test the correlation of GCG implementation, fundamental factors and company’s market performance. The samples are companies which listed in IDX from 2010-2013, have complete financial datas, and have CGPI value which released by The Indonesia Institute of Corporate Governance (IICG) from 2010-2013. The result shows that only ROE and DER variables which have significant impact to PBV at the level of significance (α) 10%. While CGPI, ROA, growth and firm size variables do not have significant impact to PBV. Those  results show that the benefit of GCG implementation to create added value to the stakeholders is still can be reflected well yet in Indonesia because of the variation of the GCG implementation that caused by the lack of strict legal rules regarding to the GCG implementation and also lack of awareness about the need of GCG implementation. Hence, IDX as one of the regulator in Indonesian Capital Market is expected to have a strict rule regarding to GCG implementation of Listed Companies and able to improve the awareness of Listed Companies, investors, and all parties in Indonesian Capital Market about the importance of GCG implementation through educational programs, seminars, and the other forms of coaching as well as incentive and reward programs. The budget to implement those plans could use budget of routine activities as well as budget specialized for workshop or seminar activities in IDX. Keywords: Good Corporate Governance (GCG), Corporate Governance Perception Index (CGPI), ROE, DER, Multiple Regression , Bursa Efek Indonesia (IDX).